Lifestyle and adaptation of retired teachers in Malaiman School Group, Nakhon Pathom Province - เกิดแจ้ง ปัทมาพร; ธรรมอภิพล สวรรยา (Journal of Liberal Arts Prince of Songkla University, 2018)
The objective of this research was to explore lifestyle and adaptation of retired teachers in Nakhon Pathom Province. Interviews were used to collect data from retired teachers in Malaiman School Group, Nakhon Pathom Province. Triangulation was used for data validation before the data were categorized, concluded, and a report was written using descriptive analysis. The results showed that the lifestyle of the retired teachers were as follows: 1) Activities—They still work to earn some money in spite of having monthly pension; they exercise, relax, and buy consumer and medical products, and enjoy parties with family and friends. 2) Opinions—They have positive thinking of self-esteem on their work, and negative thinking on their health problems. 3) Interests—Most of them give importance to health care, food choice, house cleaning, working after retirement, taking care of their family, and receiving information from outside. The adaptations of the retired teachers are as follows: 1) Physical health—They attach importance to annual health checkup, exercising, eating and relaxing; 2) Motivation—They are aware of their weak physical health, and changes of their social roles; and 3) Socially—They go to fewer social gatherings, choose to attend only important ones, and they travel less.